Non-invasive positive pressure ventilation for a severe legionella pneumonia case - (:unkn) unknown (My University, 2009)
Legionella pneumonia has a serious clinical course and requires treatment at intensive care unit. The need for mechanical ventilation is one of the determinants of prognosis. Mortality rate is higher in patients treated with mechanical ventilation. Non-invasive positive pressure ventilation (NPPV) provides mechanical ventilation without endotracheal intubation and decreases the incidence of ventilator associated pneumonia. It is a treatment modality for patients with hypoxia due to community acquired pneumonia. The present case was admitted to intensive care unit with a diagnosis of legionella pneumonia, and his hypoxemic respiratory failure was successfully treated with NPPV.
Keywords: Adult; Humans; Treatment Outcome; Male; Positive-Pressure Respiration; Community-Acquired Infections; Pulmonary Ventilation; Pneumonia, Bacterial; Legionella pneumophila; Legionnaires' Disease